The policies for expanding educational opportunities in Brazil and the school trajectories in the education of young people and adults in high school in Rio de Janeiro - Elionaldo Fernandes Julião; Mônica Dias Peregrino Ferreira (Arizona State University, 2018)
School expansion policies in Brazil, designed from the 1990s, increased the population's access to fundamental education, reaching 98.2% of the resident population in the age group from 6 to 14 years old in 2010. However, according to data released by the Brazilian Institute of Geography and Statistics in 2012, illiteracy still reaches 8.6% of the population aged 15 or older; 8.1% of young people between 18 and 24 years of age still attends elementary school , 34.2% high school and 51.3% higher education. The data shows that although we are universalizing access to elementary education in the age group of 6 to 14 years, we still suffer the result of a large number of young people who, due to problems of retention and evasion, remain, out of school, or in a situation of school lag. Considering such questions, this article, which is based on the results of a research on secondary school and in youth and adult modality conducted in the State of Rio de Janeiro in Brazil, aims to reflect about the expansion of compulsory basic education in the country and the effects of this expansion considering the school trajectories in the modality.